Common Fixed Point Results in \(C\)-Complete Complex Valued Metric Spaces - Pal, Rita; Dubey, A. K.; Pandey, Mithilesh Deo (Communications in Mathematics and Applications, 2020)
In this paper, we establish some common fixed point theorems involving two pairs of weakly compatible mappings satisfying rational inequality in the setting of \(C\)-complex valued metric space. The presented theorems generalize, extend and improve the known results in the literature.